Efficient Use of Workplace in Production - Abdujabborov Obidjon Oribjonovich; Normatov Islomiy Ilxombek o’g’li; Isroilov Asadbek Ilhomjon o’g’li; Otabek Shavkatov Kozimbek o’g’li (Genius Journals, 2022)
Meeting unlimited needs from limited resources is one of the most pressing issues today. If we look at the limited resources in the example of an enterprise, this is seen in the example of the time spent on raw materials, people and production. There are two types of time spent in the production process: those that add value to the product and those that do not add value to the product. Second, we can reduce the cost of the product by optimally reducing the time it takes to add value to the product. This article focuses on how to achieve cost-effectiveness in enterprises through the efficient use of the workplace and the proper organization of the workplace, as well as the prevention of potential inconveniences. The aim of the work is to introduce 5 C of the Japanese manufacturing industry methods of effective workplace organization to local enterprises and ultimately to prevent losses. The article provides analysis tables for the introduction of the 5C method and information on the proper organization of the workplace. A student who understands the article well will learn more about how to be effective in the workplace. And based on this information, they will be able to manage and improve their workplace
Keywords: Seiri; Seiton; Seiso; Shitsuke